EMPLOYMENT AND GENDER DISPARITY IN INDIA- A STATE LEVEL ANALYSIS - Singh Bhullar, Dr. Gurinder Jit (Innovative Research Thoughts, 2017)
This paper examines gender disparity in employment during the period 1991-2011. The results of the study noted that overall male and female workforce participation rate increased during the studied period. The rural urban decomposition of male-female workforce participation rate revealed that gender gap in workforce participation rate in rural areas shown decreasing trends, while gender gap almost remained stagnant in the urban areas during the studied period. The results of gender employment disparity index showed that at the national level gender disparity in employment status has declined during the studied period.